Evaluating the business studies curriculum for contemporary business practices - Mngwengwe, Simphiwe; Govender, Samantha; Mokoena, Sello (Edelweiss Applied Science and Technology, 2025)
The disconnect between theoretical knowledge and practical application in the Business Studies curriculum is a pressing concern, especially in developing nations like South Africa. Rapid changes in business environments and global economic trends necessitate aligning the curriculum with contemporary business practices. This study evaluates the effectiveness of the current Business Studies curriculum in preparing learners for real-world challenges and proposes strategies for improvement. The analysis, based on literature from 1970 to 2024 from publishers like Sage, Taylor & Francis, and Springer, and teachers’ perspectives, identified gaps between theory and practice. Key findings reveal that while the curriculum provides a robust theoretical foundation, it lacks practical application, leaving learners ill-prepared for the workforce. Innovative pedagogical strategies, such as project-based learning, experiential activities, and real-world simulations, are essential to bridge this gap. The study emphasizes the importance of cultivating critical thinking, problem-solving, and entrepreneurial skills through tailored teaching methods. Successful implementations of practical learning models in other contexts demonstrate the benefits of integrating such strategies into the curriculum. Recommendations include targeted teacher training programs and fostering partnerships between schools and businesses to provide learners with exposure to authentic business environments, enhancing their readiness for future career challenges.